Study of Mo3NiB3 and Mo2NiB2 cermets by first-principles calculation and experiment - Ming Yu; Xuechen Zhang; Wenhu Li; Taotao Ai; Hongfeng Dong; Zirun Yang (Next Materials)
In this work, the mechanical properties of Mo3NiB3 and Mo2NiB2 phases in Mo-Ni-B cermets were studied. The first-principles calculation results demonstrate the thermodynamic and mechanical stability of both Mo3NiB3 and Mo2NiB2. Among them, Mo2NiB2 shows superior stability and toughness compared to Mo3NiB3. On the other hand, the Young’s modulus and hardness values of Mo3NiB3 are higher than those of Mo2NiB2. Mo3NiB3 exhibits enhanced isotropy and stronger covalent bonding properties, as confirmed by DOS and Mulliken analysis. Further research shows that Mo3NiB3 has brittleness (B/G = 1.586) and high Vickers hardness (22.3 GPa), indicating its potential use as a wear-resistant material. To validate the accuracy of the theoretical calculations, Mo3NiB3 and Mo2NiB2 cermets were fabricated through vacuum hot pressing sintering, followed by comprehensive analysis of their microstructure and mechanical properties. Specifically, the experimentally measured compressive strength and hardness values of Mo3NiB3 (3213.2 MPa and 3264.2 HV0.3, respectively) were closely matched by the theoretical predictions. Notably, these experimental findings are in good agreement with the theoretically calculated values. This investigation provides reference value for a more in-depth analysis of the mechanical properties of Mo-Ni-B cermets, provides a theoretical and practical basis for its application in the field of materials, and promotes the development of Mo-Ni-B cermets materials.